Pathways to legal permanence for a cohort of care experienced children in Scotland - Hooper, Jade; Cusworth, Linda; Matthews, Ben (International Journal of Population Data Science, 2025)
Objectives Permanently Progressing is the largest longitudinal study of care experienced children in the UK and tracks the pathways and progress of a cohort of children who became looked after in Scotland in 2012/13 when aged five and under. The administrative data strand of the project aims to describe the care placement pathways and permanence status of children ten years later. Methods In Phase 2 of the project, we analysed the newly created Administrative Data Research longitudinal Children Looked After Statistics (CLAS) dataset for our full cohort of 1,836 children, covering care histories spanning from 2007-22. Using descriptive statistics, data visualization and survival analysis we used CLAS data to describe how children moved into and out of care, how many children were placed in placements intended to be legally permanent and how long this took. Results By the end of July 2022, the majority (79%) of the 1,836 children were living in homes intended to provide permanence. Overall, the median time to permanence for children was 32 months – more than two and a half years. Over 10% of children were still (or again) in impermanent placements, and for almost 10% of children there was not enough detail in CLAS to say where they were living. Conclusion Administrative data provide an invaluable window into young people’s care experiences and pathways. Whilst most of the Permanently Progressing cohort were, in July 2022, living in homes where it is anticipated they will remain until adulthood, the relatively long average time to permanence will be of concern to children and families, policy makers, and practitioners.